2022
DOI: 10.3390/math10122029
|View full text |Cite
|
Sign up to set email alerts
|

Home Production: Does It Matter for the Korean Macroeconomy during the COVID-19 Pandemic?

Abstract: The COVID-19 pandemic has had a tremendous influence on many aspects of life in Korea. Some people have had to relocate their workplaces from factories or offices to their homes in order to stop the spread of the virus. This paper examines the effects of home production on the Korean macroeconomy during the COVID-19 pandemic. Then, the impulse response function is used to perform an empirical analysis. The results show that total output, market goods consumption, investment, capital, and market work hours all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Second, our results revealed that participating in the government-sponsored program for customer and business adaptation is not the key to the MSMEs' survivability during this recovery period. These results are in contrast with the findings in the literature reported during the peak of the COVID-19 crisis (e.g., [7,[51][52][53]). Thus, the government-sponsored program should be revised appropriately to meet the demands of the current situation.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, our results revealed that participating in the government-sponsored program for customer and business adaptation is not the key to the MSMEs' survivability during this recovery period. These results are in contrast with the findings in the literature reported during the peak of the COVID-19 crisis (e.g., [7,[51][52][53]). Thus, the government-sponsored program should be revised appropriately to meet the demands of the current situation.…”
Section: Discussioncontrasting
confidence: 99%
“…In calibrating the parameters of this investigation, an effort was made to ground our selection in the scholarly literature specifically devoted to the South Korean context. In accordance with the work of He and Lee [44] and He [48], the parameter characterizing the disutility of labor was fixed at 0.34 (Ω = 0.34), thereby representing the burden associated with labor in our model. In addition, the discount factor, which underscores the time preference of consumers, was set at a value of 0.99 (β = 0.99), substantiating the notion of a high predilection for immediate over future consumption.…”
Section: Parameter Calibration and Estimationmentioning
confidence: 99%
“…In the parameter calibration phase of this study, we anchored our choices in the academic literature explicitly pertaining to the Chinese sphere. Guided by the studies of Yang et al [47] and He [48], we selected a discount factor of 0.99. The proportion of domestic goods in consumption, influenced by the research of Jin et al [49], Wang and Yao [50], and Ma [51], was established at a value of 0.5.…”
Section: Parameter Calibration and Estimationmentioning
confidence: 99%